2015
DOI: 10.1111/joca.12075
|View full text |Cite
|
Sign up to set email alerts
|

Saving, Selling, Earning, and Negotiating: How Adolescents Acquire Monetary Lump Sums and Who Considers Saving

Abstract: This study examines the importance of saving during adolescence as one way of obtaining larger sums of money, and investigates differences between adolescents who choose to save and those who do not. To this end, the strategies “saving,” “negotiating,” “selling,” and “earning” are taken into account in designing a questionnaire. Two measures of saving behaviors are used: “general tendency to save” and “saving by adjusting expenditure” when faced with an income constraint. The sample consists of 470 British sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
0
9
0
1
Order By: Relevance
“…In this group of research, age is the main focus during discussions of how children become consumers in different consumption domains. For instance, some studies examine children's consumer development from the point of sales promotions (Boland et al, 2012), money perceptions, money use, or financial attitude development (Drever et al, 2015; Fiates et al, 2008; Friedline, 2015; Otto & Webley, 2016; Ribeiro et al, 2018). Children's consumer development from the point of value perception is also examined, such as children's value perceptions in decision‐making (Williams et al, 2016), their valuation of objects for meeting important goals (John & Chaplin, 2019), and assessment of products' perceptual attributes (Wang & Li, 2019).…”
Section: Key Research Areasmentioning
confidence: 99%
“…In this group of research, age is the main focus during discussions of how children become consumers in different consumption domains. For instance, some studies examine children's consumer development from the point of sales promotions (Boland et al, 2012), money perceptions, money use, or financial attitude development (Drever et al, 2015; Fiates et al, 2008; Friedline, 2015; Otto & Webley, 2016; Ribeiro et al, 2018). Children's consumer development from the point of value perception is also examined, such as children's value perceptions in decision‐making (Williams et al, 2016), their valuation of objects for meeting important goals (John & Chaplin, 2019), and assessment of products' perceptual attributes (Wang & Li, 2019).…”
Section: Key Research Areasmentioning
confidence: 99%
“…Families' financial activities such as opening a bank account, giving pocket money, conversation about savings and money issues, allowing children to observe money transactions influence youth in shaping and developing knowledge, skills and right attitude (Agnew, 2018). Evidence also shows that students develop a financial economic understanding, skills, and habits not just by talking with parents but also through their personal experiences, and learning by doing (Otto & Webley, 2016). This proved that greater prevalence roles plays by parents in socialize their children and financial activities is considered as major force in educating children on money management effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parents who are active in socialising and influencing good financial behaviour and practices will encourage their children to practise higher degree of financial literacy (Grohmann, 2018). Additionally, literatures has shown that parent-youth relationship and its impact can be proven in many aspects of youth life, such as increased knowledge, financial planning, saving, economic orientation, household wealth, asset ownership and economic socialisation (Bucciol & Veronesi, 2014;Hira, Sabri, & Loibl, 2013;Kim, Yang, & Lee, 2015;Otto & Webley, 2016). These evidence clearly indicates that PFS is able to develop youths' competencies, subsequently encouraging youth to behave prudently and practising positive financial behaviour in their daily financial life.…”
Section: Pfs Relationship With Positive Financial Behaviourmentioning
confidence: 99%
“…Norvilitis and Mendes-Da-Silva (2013) showed that parenting plays pivotal roles in shaping students' positive or negative attitude towards money. Irrespective positive or negative FA influence by socialisation agents, it carried significant impact on youth financial management behaviour (Otto & Webley, 2016). In particular, FA that acquired and developed at early life age, may carry over and become significant predictors of consumption behaviours.…”
Section: B Determinants Of Financial Attitudementioning
confidence: 99%